2012
DOI: 10.1167/iovs.12-10367
|View full text |Cite
|
Sign up to set email alerts
|

Intraocular VEGF Level as a Risk Factor for Postoperative Complications after Vitrectomy for Proliferative Diabetic Retinopathy

Abstract: High intraocular VEGF level at the time of primary vitrectomy in patients with PDR was identified as a significant risk factor for postoperative early VH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
54
3
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 52 publications
(67 citation statements)
references
References 32 publications
3
54
3
2
Order By: Relevance
“…This implies the high prognostic value of VEGF-A levels >137.4 pg/mL in evaluating the risk of complications and their onset times. Similar results were reported by Wakabayashi et al [25]. They assessed the vitreous and ACL level of VEGF as a significant risk factor for the early post-operative hemorrhage and NVG development.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…This implies the high prognostic value of VEGF-A levels >137.4 pg/mL in evaluating the risk of complications and their onset times. Similar results were reported by Wakabayashi et al [25]. They assessed the vitreous and ACL level of VEGF as a significant risk factor for the early post-operative hemorrhage and NVG development.…”
Section: Discussionsupporting
confidence: 87%
“…Moreover, NG due to PDR is associated with extremely high VEGF level. Several authors [22, 23] demonstrated the elevation VEGF value in the glaucomatous eyes and the benefits of the blockage of the VEGF in the eye [24, 25]. In this way, VEGF-A levels in ACL are associated with the severity of DR.…”
Section: Discussionmentioning
confidence: 99%
“…Funatsu et al [18] previously reported cases in which the retinopathy was aggravated after a vitrectomy and speculated that the levels of intravitreal VEGF and endostatin were involved. Wang et al [19] also demonstrated that there was an association between the VEGF level and the progression of postoperative retinopathy, while Wakabayashi et al [17] reported finding a correlation between postoperative complications and the intravitreal VEGF level.…”
Section: Discussionmentioning
confidence: 99%
“…Following a vitrectomy, it is further anticipated that with higher intravitreal VEGF levels, there will be more frequent postoperative complications and a worse postoperative visual acuity. Although a few studies have reported similar findings, these issues have yet to be sufficiently examined [17,18,19]. Therefore, the present study examined the relationship between the intravitreal VEGF level and the frequency of surgical complications in PDR patients who underwent a vitrectomy.…”
Section: Introductionmentioning
confidence: 87%
See 1 more Smart Citation